Teatro infantil en el fortalecimiento de la autoestima en educación inicial (2018)
The selfesteem is a global valuation brings over of if same, it can be translated in a perception of being querible, valuable to be satisfied to be since is; or on the contrary, in a feeling of being slightly valuable, not querible, a negative feeling of not acceptance I concern of yes same being significant in the school age. The aim of investigation is to form an offer of didactic - pedagogic nature that based on scenic arts, as the theatre, east the strengthening of the selfesteem in initial education of the Educational Institution N º 3 Sedates San Jose of the Municipality Maicao. The population was constituted by twenty-five children of Transition school period 2016-2017. Framed in the positivist paradigm, quantitative approach, type and design of investigation cuasi experimental, as technologies of compilation of information the direct observation in application of the questionnaire Protocol structured TAE-TEACHER, with 19 Itemes. Concluding that on having formed the offer of didactic - pedagogic nature based on scenic arts, as the theatre before of the TAE-TEACHER to apply and after the treatment; they take implicit activities of learning that establish a relation between theatre, education and selfesteem in the children.